2019
DOI: 10.1155/2019/1751783
|View full text |Cite
|
Sign up to set email alerts
|

Acetotrophic Activity Facilitates Methanogenesis from LCFA at Low Temperatures: Screening from Mesophilic Inocula

Abstract: The inoculum source plays a crucial role in the anaerobic treatment of wastewaters. Lipids are present in various wastewaters and have a high methanogenic potential, but their hydrolysis results in the production of long chain fatty acids (LCFAs) that are inhibitory to anaerobic microorganisms. Screening of inoculum for the anaerobic treatment of LCFA-containing wastewaters has been performed at mesophilic and thermophilic conditions. However, an evaluation of inocula for producing methane from LCFA-containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Gelria is a thermophilic, anaerobic, obligately syntrophic, glutamate-degrading genus, usually found in granular sludge within anaerobic sludge bed reactors [53]. The genus Syntrophus (positively influenced by Al-p-value = 0.004, Fe-0.030, Cr-0.016, Ni-0.004, and Co-0.027) is responsible for methane production and was found to be correlated to Gelria for treating the mixed-LCFA (long-chain fatty acids) at low temperature in municipal wastewater plants [54]. Syntrophus-associated sequences have been identified in anoxic sediments and sewage sludge [48].…”
Section: Resultsmentioning
confidence: 98%
“…Gelria is a thermophilic, anaerobic, obligately syntrophic, glutamate-degrading genus, usually found in granular sludge within anaerobic sludge bed reactors [53]. The genus Syntrophus (positively influenced by Al-p-value = 0.004, Fe-0.030, Cr-0.016, Ni-0.004, and Co-0.027) is responsible for methane production and was found to be correlated to Gelria for treating the mixed-LCFA (long-chain fatty acids) at low temperature in municipal wastewater plants [54]. Syntrophus-associated sequences have been identified in anoxic sediments and sewage sludge [48].…”
Section: Resultsmentioning
confidence: 98%
“…The abundance of Synergistates represents the same tendency as Actinobacteria (3% in V1, 3.9% in V3, and 1.3% in V5) (Figure 6). This phylum was dominated by Synergistia, to which belong syntrophic acido-and acetogens involved in amino acid fermentation [94]. Probably due to interspecies hydrogen transfer between Synergistia and methanogens, Nakasaki and co-workers [95] observed that the abundance of Synergistales highly correlated with the rate of methane production from oil during the anaerobic digestion for treatment of synthetic lipid-rich wastewater.…”
Section: Microbial Compositions In Anaerobic Digestermentioning
confidence: 99%
“…Dairy wastewaters contain lipids that are hydrolysed into long-chain fatty acids (LCFA) that may be inhibitory to anaerobic microorganisms. Anaerobic conversion of LCFAs to methane was reported for the first time at 10°C and 20°C (with lipid content of .1%) in batch bottles, where the role of acetoclastic methanogens from the genus Methanosaeta was highlighted (Singh et al 2019). In the pulp industry, recovery of chemicals from black liquor results in the production of condensates that contain methanol up to 46 g/L.…”
Section: Technologies and Productsmentioning
confidence: 99%